The personal effectiveness of the collective agreement: Comings and goings on the unilateral extension of the collective agreement - Boza Pró, Guillermo (2024)
The unilateral extension of the collective agreement has been widely discussed by Peruvian doctrine and jurisprudence for more than a decade. Aside from this, it maintains its validity to the extent that there is still a contrast in positions between two decision-making bodies of the Peruvian labor legal system. This article addresses the topic with the purpose of establishing a position on the debate, developing its analysis in three sections. Firstly, basic issues relating to the collective agreement as a bargaining product, its legal effectiveness and its personal effectiveness related to the criterion of greater representativeness are reviewed. Secondly, the jurisprudential evolution that the topic has had in the decisions of the Supreme Court, such as those of the Labour Inspection Court of the National Superintendence of Labour Inspection, is detailed; in such a way that the authors mark their position on the arguments outlined in each case. Next, a rarely touched upon aspect of the theme is developed; that is, the possibility for non-unionized workers to retain the benefits unilaterally extended by the employer. The article ends with some brief conclusions on what has been reflected.